2013
DOI: 10.1371/journal.pone.0071932
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Activation Promotes Oncolytic HSV1 Replication in Glioma Cells

Abstract: Recent studies report that STAT3 signaling is a master regulator of mesenchymal transformation of gliomas and that STAT3 modulated genes are highly expressed in the mesenchymal transcriptome of gliomas. A currently studied experimental treatment for gliomas consists of intratumoral injection of oncolytic viruses (OV), such as oncolytic herpes simplex virus type 1 (oHSV). We have described one particular oHSV (rQNestin34.5) that exhibits potent anti-glioma activity in animal models. Here, we hypothesized that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 19 publications
2
23
0
4
Order By: Relevance
“…Cytokines and chemokines derived from oHSV-infected tumor cells or cells of the tumor microenvironment limit oHSV replication and spread within the tumor and further induce stronger innate immune responses [20,21]. Chemokines CXCL9 (MIG) and CXCL10 (IP-10) are important in limiting HSV infections, recruiting natural killer (NK) and CD8 + T cells to the CNS [21].…”
Section: Host Responses Against Hsv Infectionmentioning
confidence: 99%
“…Cytokines and chemokines derived from oHSV-infected tumor cells or cells of the tumor microenvironment limit oHSV replication and spread within the tumor and further induce stronger innate immune responses [20,21]. Chemokines CXCL9 (MIG) and CXCL10 (IP-10) are important in limiting HSV infections, recruiting natural killer (NK) and CD8 + T cells to the CNS [21].…”
Section: Host Responses Against Hsv Infectionmentioning
confidence: 99%
“…Thus, new level of control of cellular functions by HSV-1 suggests that persistent NF-κB/p65/RelA activation in HSV-1-infected cells, rather than being a host response to the virus, may play a positive role in promoting efficient viral replication [18]. As for STAT3, its signaling was shown to promote oncolytic HSV-1 replication, likely by inhibiting the IFN-γ response [19]. As virus-host interactions are crucial for the outcome of infections, our computational findings of multiple potentially active DREs in promoter region of HSV-1 genes, as well as in genes encoding major host cell cytokines, all strongly suggest that body burden subnanomolar dioxin is able to promote HSV-1 infection.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that genetic or pharmacologic activation of STAT3 in glioma cells enhanced oHSV replication and cytotoxicity [18]. And McCartney et al also proved that HCV replication increase STAT3 activation; in turn activation of STAT3 increases HCV replication by modulating microtubule dynamics Fig.…”
Section: Discussionmentioning
confidence: 97%